Global cassava research and development: the cassava demand studies and implications for the strategies for the CIAT cassava program - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
The structure and methodology of cassava research are discussed. Research on the potential world demand for the crop was divided into different components: the country was the unit of analysis and the market, the 2nd level of analytical subdivision where individual markets were assumed to be independent; the potential demand in each market was analyzed separately (market size, growth prospects, and price of competition with main substitutes). In Asia, a multiple cassava market system is already well developed. Growth markets exist for cassava to the point that production is not keeping up with demand. However, little improved production technology has reached the farm level. Declining costs of production could accelerate the diversification of markets in Asia, especially into the animal feed market. The existing market structure could absorb significant increases in production, without drastic inclines in prices. A range of benefits could be attained, including simultaneous improvements in the welfare of the low- income consumer and in the income of small-scale farmers in upland areas. On the other hand, traditional food markets continue to dominate the overall demand for cassava in Latin America; only in Brazil do traditional dried cassava products dominate in overall cassava demand. The major potential growth in demand for cassava exists in the market for animal feed components. Integrated cassava development projects have proved to be good initial interventions. (CIAT)